2021
DOI: 10.31744/einstein_journal/2021ao6289
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of primary immunodeficiency diseases at a national pediatric reference center in Peru

Abstract: Objective: To investigate the level of awareness of primary immunodeficiency diseases among physicians working at Instituto Nacional de Salud del Niño. Methods: Cross-sectional study including pediatric residents and pediatricians working at the Instituto Nacional de Salud del Niño during the study period (2017)(2018)(2019). Physicians working at the immunology unit and surgery departments were excluded. Three aspects of awareness of primary immunodeficiency diseases were investigated: education, general knowl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
0
0
0
Order By: Relevance
“…The frequency of right answers about PIDD warning indicators in children increased significantly (85.1% versus 64.6% in 2016, P0.0001), while there was no significant gain in adult awareness about warning signs [ 12 ]. This is congruent with a Brazilian study, which also found a lack of awareness of primary immunodeficiency warning symptoms [ 13 ].…”
Section: Discussionsupporting
confidence: 91%
“…The frequency of right answers about PIDD warning indicators in children increased significantly (85.1% versus 64.6% in 2016, P0.0001), while there was no significant gain in adult awareness about warning signs [ 12 ]. This is congruent with a Brazilian study, which also found a lack of awareness of primary immunodeficiency warning symptoms [ 13 ].…”
Section: Discussionsupporting
confidence: 91%
“…In a previous study, the most common warning signs of PID reported by physicians were recurrent otitis media and two or more pneumonias within one year [24]. In similar previous studies, it was observed that more than half of the physicians were not familiar with the JMF warning signs [23,24]. In this study, similarly, familiarity with JMF warning signs was not found in the majority of physicians.…”
Section: Discussionsupporting
confidence: 66%
“…In a similar previous study, the three most common clinical conditions recognized among the 10 warning signs of PID were pneumonia once a year for more than 2 years, two or more new otitis media within 1 year, and the need for recurrent intravenous antibiotics, respectively [23]. In a previous study, the most common warning signs of PID reported by physicians were recurrent otitis media and two or more pneumonias within one year [24]. In similar previous studies, it was observed that more than half of the physicians were not familiar with the JMF warning signs [23,24].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…However, the number of reported cases is lower. Several studies suggest that the lack of awareness by physicians for IEI might delay the diagnosis and the treatment of these patients (3). of COVID-19 were followed up and it was reported that the pandemic caused more than 6 million deaths (4).…”
Section: Introductionmentioning
confidence: 99%